On the Annonaceae of Sungai Menyala forest reserve, Port Dickson, Negeri Sembilan - Zohari, Ahmad Fitri; Mustafa Bakery, Nur ‘Aqilah; Zulkifli, Mohammad Khairul Faizi; Mohd Said, Mohd Nizam; Nik Hashim, Nik Hazlan; Nik Ali, Nik Norafida; Wan Ismail, Wan Norilani; Mohamad, Norazlinda; Talip, Noraini; Mohamad, Abdul Latiff (Universiti Teknologi MARA (UiTM), 2024)
A preliminary report of Annonaceae in Sungai Menyala Forest Reserve, Port Dickson, Negeri Sembilan, Peninsular Malaysia, is given. Based on the collections in the herbarium and in the field, a total of 17 genera and 24 species were listed. In the recent survey during the scientific expedition in October 2022, a total of 13 taxa were recorded, viz. Alphonsea elliptica, A. maingayi, Artabotrys suaveolens, Dendrokingstonia nervosa, Desmos dasymaschalus, Goniothalamus macrophyllus, Mezzettia parviflora, Monocarpia euneura, Phaeanthus ophthalmicus, Polyalthia rumphii, Trivalvaria macrophylla, Xylopia ferruginea and X. malayana. Only one endemic species to Peninsular Malaysia was listed, namely Drepananthus pruniferus and only one species, Monocarpia euneura, bears both flowers and fruits during the recent survey. Another species, Phaeanthus ophthalmicus, only bears flowers. These results contributed some additional information about the flowering plants in Sungai Menyala Forest Reserve.